Rarities of phytodiversity in the Bilosers’ky national natural park (CHORNOMORSKI BOTANICAL JOURNAL, 2012)
An autosozological analysis of rarities of phytogenetic fund of the national nature park "Beloozerskiy" (10 species) is given together with sinphytosozological analysis of rarities of phytocoenotic fund (18 associations).
Keywords: rarity specie , rare association, national nature park, sozological analysis.